Correlation between newborn size and gross fetal movement as counted by a fetal movement acceleration measurement recorder. (14th June 2021) - Yatsuki, Keita; Ryo, Eiji; Morita, Masayoshi; Seto, Michiharu; Kamata, Hideo; Yonaga, Yuriko
Abstract: The development of the fetal movement acceleration measurement (FMAM) recorder has enabled the accurate counting of gross fetal movements. The aim of the study was to investigate whether gross fetal movement is related to a newborn's size. A total of 90 pregnant women who delivered singleton infant at term were recruited. Gross fetal movements were counted using an FMAM recorder during maternal sleep. The ratio of movement positive 10-s epochs to all epochs during one night was calculated as an index of fetal movement. Independent explanatory variables for the fetal movement index were selected from eight possibilities, that is, maternal age, gestational week, and the six physical measures of the newborn (height, weight, head circumference, chest circumference, Kaup index, and the ratio of head to chest circumference) with the stepwise regression procedure. The selected physical variables and the fetal movement index were analyzed using multiple regression analysis. A total of 2812.95 h from 423 night records were available. Gestational weeks and weight of the newborn were selected as the significant independent variables. Multiple regression analysis revealed that newborn weight had a positive correlation with the fetal movement index ( p < 0.0001). The multiple regression equation was "The fetal movement index (%) = 34.9989−0.9088 × gestational weeks + 0.0033 × newborn weight (g)." A person's physical ability and lifetime activity level may originate from fetal health. This study may provide a new way of looking at the Developmental Origins of Health and Disease theory.